Community resilience to climate change in vulnerable urban settlements: the case of Monte Sinai, Ecuador. - Morán Parrales, Romina (2026)
Monte Sinaí, a low-income urban area located in Guayaquil, is highly exposed to environmental risks exacerbated by disorderly growth, lack of basic services, and weak institutional response. Given this scenario, the present research aims to assess the level of community resilience to climate change, with an emphasis on local adaptation capacities, social participation, and environmental governance conditions. The study was conducted in 2025 using a qualitative-descriptive approach, employing documentary analysis of official sources, technical reports, statistical data, and scientific literature, complemented by a territorial analysis matrix. The results show that the community lacks effective mechanisms to sustainably address the impacts of climate change. There are only isolated initiatives in the sector, mainly due to poor coordination between local actors, limited environmental knowledge, and structural limitations in public services. Key factors affecting the population's response capacity were identified, such as the informality of the settlement, legal uncertainty regarding land ownership, and the absence of participatory planning. Climate resilience in vulnerable sectors such as Monte Sinaí needs to be strengthened through technical interventions and a transformation in the way communities participate in environmental decision-making. It is recommended that priority be given to local environmental governance strategies that integrate education, basic infrastructure improvements, and inter-institutional coordination.